Watershed's spatial targeting: Enhancing payments for ecosystem services to scale up agroecosystem restoration through nature-based solutions - de Mendonça, Gislaine Costa [UNESP]; Abdo, Maria Teresa Vilela Nogueira [UNESP]; da Costa, Luis Miguel [UNESP]; Costa, Renata Cristina Araújo [UNESP]; Pacheco, Fernando António Leal [UNESP]; Ribeiro, Milton Cezar [UNESP]; Zakia, Maria José Brito [UNESP]; Borma, Laura De Simone; Pissarra, Teresa Cristina Tarlé [UNESP] (Elsevier, 2025)
Payment for Ecosystem Services (PES) globally addresses land use-tenure-restoration tradeoffs. The Atlantic Forest Connection Projetc, a Brazilian collaborative initiative, aimed to preserve and restore the Brazilian Atlantic Forest fostering and rewarding sustainable land use that could generate biodiversity, climate, and socioeconomic benefits through Nature-based Solutions (NbS). However, comprehensive assessments of these strategic implementations are still lacking. To validate them and enhance overall effectiveness, we have developed the PES-Catchment protocol, a watershed-based framework that targets strategic areas, and propose metrics for evaluating water and soil conservation services. This methodology seeks to optimize the impact of existing environmental and socioeconomic public policies and governance, by directing the efficient implementation of NbS in the restoration of agroecosystems. Priority areas were identified using a multicriteria decision analysis in GIS software, by merging key factors (watershed management, landscape vulnerability, water availability, land degradation) for improving landscape restoration and ecosystem services through agroforestry implementation. Three reference scenarios were created to identify where the benefits can be maximized: SI) multiple ecosystem services conservation (water and soil); SII) hydrological services provision; and SIII) land degradation neutrality. The extent of high levels of degradation across scenarios ranges from 22 to 26%, with scenario SI being the most responsive to high-priority areas. In contrast, low priority areas were more frequently observed under SII scenario, followed by SIII and SI, respectively. The projections prioritized 25% of the area along the most critical catchments and subbasins, exposing a significant level of land degradation and risks to hydrological services. Furthermore, around 50% of the private rural properties registered in the programs are distributed in medium priority areas, and 21% on average are in high-priority areas, which represents an alert to redirect targets and intensify the efforts in resource allocation (implementing/monitoring). The PES – Catchment outcomes offer insights and structural support to adjust governance strategies, optimizing payments for ecosystem services aimed at landscape restoration and watershed conservation.
Keywords: Agroforestry; Environmental services; Land degradation; Land use policy; Soil and water conservation; Spatial modeling